Amygdala subnuclei volumes, functional connectivity, and social–emotional outcomes in children born very preterm. Issue 3 (22nd July 2022) - Mueller, Megan; Thompson, Benjamin; Poppe, Tanya; Alsweiler, Jane; Gamble, Greg; Jiang, Yannan; Leung, Myra; Tottman, Anna C; Wouldes, Trecia; Harding, Jane E; Duerden, Emma G; ,
Abstract: Children born very preterm can demonstrate social-cognitive impairments, which may result from limbic system dysfunction. Altered development of the subnuclei of the amygdala, stress-sensitive regions involved in emotional processing, may be key predictors of social-skill development. In a prospective cohort study, 7-year-old children born very preterm underwent neurodevelopmental testing and brain MRI. The Child Behavioral Checklist was used to assess social–emotional outcomes. Subnuclei volumes were extracted automatically from structural scans ( n  = 69) and functional connectivity ( n  = 66) was examined. General Linear Models were employed to examine the relationships between amygdala subnuclei volumes and functional connectivity values and social–emotional outcomes. Sex was a significant predictor of all social–emotional outcomes ( P  < 0.05), with boys having poorer social–emotional outcomes. Smaller right basal nuclei volumes ( B  = -0.043, P  = 0.014), smaller right cortical volumes ( B  = -0.242, P  = 0.02) and larger right central nuclei volumes ( B  = 0.85, P  = 0.049) were associated with increased social problems. Decreased connectivity strength between thalamic and amygdala networks and smaller right basal volumes were significant predictors of greater social problems (both, P  < 0.05), effects which were stronger in girls ( P  = 0.025). Dysregulated maturation of the amygdala subnuclei, along with altered connectivity strength in stress-sensitive regions, may reflect stress-induced dysfunction and can be predictive of social–emotional outcomes.